Enhancing and Monitoring Impacts of Complementary and Linked Land and Water Management Technologies and Approaches at Landscape/Watershed Levels - International Water Management Institute; International Center for Tropical Agriculture (International Food Policy Research Institute, 2018)
This dataset originated from the CIAT led project entitled ?Enhancing and monitoring impacts of complementary and linked land and water management technologies and approaches at landscape/ watershed levels.? The data were collected at the sites after CIAT implemented runoff plots. The data collected includes biomass yield, grain yield, and soil depth and moisture to measure the effect of soil and water conservation structures on soil moisture and wheat yield.